Right Internal Carotid Artery Occlusion during Intravenous Thrombolysis for Left Middle Cerebral Artery Occlusion - Yalcin-Cakmakli, Gul; Akpinar, Erhan; Topcuoglu, Mehmet Akif; Dalkara, Turgay (Journal of stroke and cerebrovascular diseases, 2009)
Thrombolysis with recombinant tissue plasminogen activator is the only established treatment for acute ischemic stroke. Recurrent ischemic stroke involving an initially unaffected arterial territory during the course of thrombolysis has been reported but remains exceptionally rare. Here we report a 75-year-old woman with acute left middle cerebral artery occlusion who developed right internal carotid artery occlusion during the last minutes of recombinant tissue plasminogen activator infusion. Although the transthoracic echocardiography did not reveal an intra-atrial thrombus, cardioembolism due to disintegration of a pre-existing thrombus was thought to be the underlying mechanism because the patient had atrial fibrillation. Arterial occlusion due to intraplaque hemorrhage and de novo thrombosis caused by thrombin-mediated platelet aggregation are also discussed as potential mechanisms of arterial occlusion.